MODELING, VARIABLES INFLUENCE AND OPTIMIZATION USING RESPONSE SURFACE METHOD – CENTRAL COMPOSITE DESIGN (RSM-CCD) ON THE SODIUM LIGNOSULFONATE PRODUCTION FROM - Amun Amri; Zulfansyah Zulfansyah; M. Iwan Fermi; Is Sulistyati; Ani Suryani; Erliza Hambali (Reaktor, 2009)
The sodium lignosulfonate (SLS) is a derivative compound from lignin which has various usefulness. Commercial SLS is a by-product of Arbiso pulping sulfite industry, but nowadays, the amount of available commercial SLS is scare due to the expensive price of SLS. Therefore, it is needed to find the solution to produce of SLS using a feasible process. This research involves producing SLS by directly cooking the palm oil stem biomass dust in a pressurized reactor using sodium bi-sulfite (NaHSO3) solvent. The experiment focused on the modeling, influence of process variables and its optimization that statistically analyze using the Response Surface Method-Central Composite Design (RSM-CCD). The result showed that the solid-liquid ratio is the most affecting factor to the SLS rendemen. The relation between rendemen and temperature (T), pH (C) and solid-liquid ratio (R) can be modeled as % rendemen = 12.18 + 0.52T – 0.48C + 3.5R – 1.02T2 – C2 – 1.53R2. The optimal operation conditions were identified at temperature of 153.8oC, pH = 4.64 and solid-liquid ratio of 1:15.9.